Solvent Extraction of Cd(II) using n-Butylamine-ClO:-MIBK and n-Butylamine-Oxine-MIBK - Tan, Wee Tee; Wong, See Keong (1992)
n-Butylamine-perchlorate-1WJBK and n-butylamine-oxine-MIBK extractants were found to be effective for the extraction of Cd(II) ions under strongly alkaline conditions (pH>10). This extraction is a function of the concentration of oxine, perchlorate, n-butylamine and pH. The flame AAS signal for Cd(II) was considerably enhanced by using the above extractants. The signal enhancement and the increase in % extraction of Cd(II) can be attributed to the formation of synergistic amine adducts.